EFFECT OF CUMULATIVE EXPOSURE TO SILICA DUST ON RESPIRATORY SYMPTOMS IN UNDERGROUND MINERS - Latkoska, Sanja; Minov, Jordan; Velic Stefanovska, Vesna (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction. Occupational exposure to silica dust may lead to respiratory symptoms, lung function decline, morbidity, disability and mortality.  Aim of the study. To assess the impact of estimated cumulative exposure to silica dust on respiratory symptoms in underground miners. Methods: A cross-sectional study included 320 male underground miners divided in two groups by their work tenure (<15 and >15years). Study protocol included completion of a questionnaire on demographics and respiratory symptoms (cough, phlegm, dyspnea, wheezing and chest tightness) in the last 12 months and grade of sypnea, measurements of respirable dust and crystalline silica and calculation of cumulative exposure to silica dust.  Results. Mean estimated cumulative exposure to silica dust in the underground miners with work tenure equal or less than 15 years was 0.06±0.03 mg/m 3 , whereas mean estimated cumulative exposure to silica dust in the underground miners with work tenure longer than 15 years was 0.15±0.04 mg/m 3 . A significant association was found between the work tenure (<15/ >15 years) and the presence of respiratory symptoms (15.83% vs. 36.11%, p=0.00001). A significant linear positive correlation was found between the presence of respiratory symptoms and the work tenure (p=0.00001) and the estimated cumulative exposure to silica dust (p=0.00001).  Conclusion. We found significant impact of cumulative exposure to silica dust on respiratory symptoms, indicating a need of improvement of preventive measures and activities in order to protect respiratory health of underground miners.  Key words: crystalline silica, estimated cumulative exposure, respiratory symptoms in the last 12 months, underground miners, work tenure.